THE USE OF PROBLEM BASED INSTRUCTION MODEL TO MOTIVATED THE INDEPENDENT BIOLOGICAL LEARNING TOWARD THE STUDENT OF SMP 16 BANDAR LAMPUNG IN ACADEMIC YEAR OF 2004/2005 - JALMO, TRI; PURWADI, PURWADI (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
This is a colaborative action research which carried out toward student of SMP Negeri 16 Bandar Lampung. The aim of this research was enhancing the self learning motivation by using Problem Based Instruction (PBI) model. The research conducted in 2 cycles, using the criteria of teacher 's performance and student ’s ability toward biological learning The data awas then analized and intepreted to show the improving teacher performance for each cycle.The result showed that the teacher was a good fascilitator (score 2,98 in cycle I and 2,93 in cycle), so it ’s able to enhace the self learning motivation of a student, indicated with the increasing point of the readiness of study, the higly motivated in answer and question interaction, ability in answering the questions, giving opinion, creative, and highly initiative to study. That self learning motivation then gives rise to the average class mark even its equitability thus showed the better teaching and learning proccesses.